PENGARUH METODE KOOPERATIF TIPE THINK TALK WRITE (TTW) TERHADAP KETERAMPILAN MENULIS BERITA SISWA KELAS VIII SMP NEGERI 3 PARIAMAN - Dwi Mutia Chan (FKIP UMSB, 2017)
This study aimed to describe. First, news writing skills of students before the applied methodcooperative type think talk write. Second, news writing skills of students after the methodcooperative type think talk write.Third, the difference between news writing skills students before and after the applied method cooperative type think talk write. This research is quantitative experimental method. The data in this study is the result of news writing skills score of eighth grade students of SMP Negeri 3 Pariaman. The sample in this study - the eighth grade students of SMP Negeri 3 Pariaman were 30. The results of this study are:first, news writing skills of students before the applied methodcooperative type think talk write with an average value of 62.66 with sufficient qualifications. Second, news writing skills of students after the applied methodcooperative type think talk write with an average value of 80.76 with good qualifications. Third, there is a difference between news writing skills of students before and after the applied methodcooperativetypethink talk write at the 0.05 significance level with n - 2 degrees of freedom. Thus,in this study rejected H_0 , H_1 acceptable because the test results prove that Tcount > Ttabel is greater than 8,4> 2,04 at P 0.05. Keywords: Influence, Method Cooperative Type Think Talk Write, News.